Optimization of EDM process parameters in machining Si3N4–TiN conductive ceramic composites to improve form and orientation tolerances. (October 2016) - Selvarajan, L.; Sathiya Narayanan, C.; Jeyapaul, R.; Manohar, M.
Abstract: In this research, investigational and experimental work was carried out on the electric discharge machining (EDM) of a Si3 N4 –TiN ceramic composite using a copper electrode as the EDM tool. These composites are used in high-temperature environments, such as in metal forming, extrusion dies, turbine blade and non-ferrous molten metal handling components. The Si3 N4 –TiN composite is difficult to machine using conventional machining techniques. However, it can be easily machined using a spark EDM process to obtain accurate dimensional and geometric tolerances. The machining parameters, such as the current ( I ), pulse on time ( T on ), pulse off time ( T off ), dielectric pressure (DP) and spark gap voltage (SV), were investigated using a Taguchi L25 orthogonal array. The output characteristics, such as the material removal rate (MRR), tool wear rate (TWR), wear ratio (WR), surface roughness (Ra), top radial over cut (ROCTop ), bottom radial over cut (ROCBottom ), taper angle ( θ ), circularity (CIR), cylindricity (CYL), perpendicularity (PER) and run out (RO), were examined during the sparking operation. The significance of the machining parameters was obtained using analysis of variance (ANOVA) based on grey relational analysis (GRA), which showed that the current, pulse on time and spark gap voltage were the most significant parameters. The results were further confirmed using an experiment that illustrated that the spark eroding process could effectively be improved.